Religiosity, Halal Tourism Meaning, and Visit Intention: A Phenomenological Study of Muslim Tourists - Riya Zulfa Lutfiyati; Nur Choirul Afif (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Halal tourism is booming as Muslim travelers increasingly seek trips that honor their faith without compromise. This study aims to analyze the role of religiosity as a mediator in the relationship between the meaning of halal tourism and the intention of Muslim tourists to visit. Using a phenomenological approach, this study explores the subjective experiences of Muslim tourists in understanding the concept of halal tourism. Data were collected through in-depth interviews with Muslim tourists who had visited halal tourism destinations, then analyzed using thematic analysis. The results show that the level of religiosity plays an important role in shaping positive perceptions of halal tourism and strengthening the intention to visit. Tourists with higher levels of religiosity tend to perceive halal tourism not only as a facility that supports worship, but also as part of fulfilling religious values in travel. These findings contribute theoretically to the development of halal tourism marketing by incorporating religiosity as a key factor. Practically, the research results can be a reference for managers and developers of halal tourism destinations in designing marketing and destination development strategies that are more in line with the needs of Muslim tourists.